KAJIAN LIVING QUR’AN: TRANSFORMASI ILMU PENGETAHUAN PENGKAJIAN TAFSIR TAHLILY DI MASJID NURUT TAQWA SONO SINDUADI MLATI - Muhammad Sakti Garwan (AL-TADABBUR, 2019)
Social events related to attending the Qur’an or receiving the Qur’an in a particular Muslim community become a complete facility to add to the benefits of people's lives. From there it will also be seen the social response (reality) of the Muslim community to make life and live the Qur'an alive through a continuous interaction. The living Qur'an is a study based on the Qur'anic phenomenon in daily life, namely the meaning and function of the Koran which is actually translated and understood by Muslim societies. In this study, the Qur'anic life study discusses using qualitative descriptive descriptions, also using the results of interviews, observations and documentation as the primary data source in this study conducted at the Nurut Taqwa mosque in the village of Sono Sinduadi Mlati, which where this society does some Islamic values that are relevant to the assessment of the Qur'an's life is the study of Qur'anic interpretations using the tahlily method, which as a form of educating morals and aqeedah also establishes good friendship between communities in the village community framework in the village can help change knowledge by representing the study